Karakteristik anatomi dan energi kayu dari tiga tumbuhan invasif [Anatomical and energi characteristics of wood from three invasive species] - Rahmadani, Silmi Yusri; Alponsin, Alponsin; Maideliza, Tesri; Jannatan, Robby (Jurnal Riset Industri Hasil Hutan, 2021)
The presence of invasive species is often seen as environmental and economic problem. On the other hand, the potential of these species which have fast growing and regeneration ability can be used for various purposes such as alternative bioenergy utilization. This study is aimed to observe the wood anatomical and energy characteristics of invasive species such as Melastoma malabathricum, L., Calliandra callothyrsus, Meissn and Acacia mangium, Willd. It is potentially utilized as source of alternative energy. This study used purposive sampling method, and used wood samples with the thickness of about ≥5 cm. This research was analyzed descriptively for anatomy characteristic whereas the diameter and frequency of vessel, heigh and width of parenchyma then calorific value, ash and moisture content analyzed using Kruskall Wallis and Mann Whitney. Anatomical characteristic of wood from two species were diffuse porous vessel, solitary and multiple vessel, frequency of vessel were rare to many and diameter of vessel were small to rather small and paratracheal axial parenchyma. Rays were uniseriate or biseriate with 1-3 seriate, height of ray category was extremely short and width rays were narrow to extremely narrow. All rays were homorocelular with upright or procumbent cells. The calorific value of these species started from 3,887.59 to 4,132.99 kal/g. Ash content start from 1.27–1.73% meanwhile the moisture content were 11.6–12.6%. Base on energy properties, Calliandra callothyrsus, Meissn. fulfilled the standard of bio pellet production base on SNI 8021 and EN- 14961-2.